Asthma Therapies on Pulmonary Tuberculosis Pneumonia in Predominant Bronchiectasis–Asthma Combination - Yeh, Jun-Jun; Lin, Hui-Chuan; Yang, Yu-Cih; Hsu, Chung-Y.; Kao, Chia-Hung (Frontiers in Pharmacology, 2022)
Background: It is sometimes difficult to distinguish between asthma and bronchiectasis as their symptoms overlap, and these two diseases are associated with pulmonary tuberculosis (PTB) or pneumonia. Objective: To determine the effects of bronchodilator drugs, steroids, antidepressants drugs, and antianxiety drugs on the risks of (PTB or pneumonia) in patients with ((bronchiectasis–asthma combination) or (bronchiectasis—asthma-chronic obstructive pulmonary disease combination)) -BCAS cohort. Methods: After propensity score matching, we retrospectively studied patients with BCAS cohort (N=620) and without BCAS cohort (N=2314) into analysis. The cumulative incidence of PTB or pneumonia was analyzed through Cox proportional regression. After adjustment for sex, age, comorbidities, and medications (including long-acting beta2 agonist/muscarinic antagonists (LABAs/LAMAs), short-acting beta2 agonist/ muscarinic antagonists (SABAs/SAMAs), leukotriene receptor antagonist, montelukast, steroids (inhaled corticosteroids, ICSs, oral steroids, OSs), anti-depressants (fluoxetine) and anti-anxiety drugs (benzodiazepines, BZDs)). We calculated the adjusted hazard ratios (aHR) and their 95% confidence intervals (95 % CI) for these risks. Similar to OSs, ICSs are associated with an increased risk of (PTB or pneumonia), lumping these two as steroids (ICSs/OSs). Results: For the aHR (95% CI), as the non-LABAs/non-OSs as the reference 1, the (LABAs 0.70 (0.52-0.94)/OSs 0.35 (0.29-0.44)) use were associated with the lower risk of the PTB or pneumonia. However, the current use of (LABAs 2.39 (1.31-4.34) /SABAs 1.61 (1.31-1.96)), steroids (ICSs3.23 (1.96-5.29)/OSs 1.76 (1.45-2.14)) and BZDs (alprazolam 1.73 (1.08-2.75)/fludiazepam 7.48 (1.93-28.9)) were associated with these risks. The current use of LAMAs 0.52 (0.14-1.84)/SAMAs 1.45 (0.99-2.11) were not associated these risks. Conclusion: The current use of LAMAs/SAMAs are relative safe with respect to (PTB or pneumonia) risks, but the LABAs/SABAs, steroids, and BZDs could be used after evaluation of the benefit for BCAS cohort. However, we must take the possible protopathic bias into account.